Answer:
--- Length
--- Width
Step-by-step explanation:
Given
Let: ![L = Length; W = Width](https://tex.z-dn.net/?f=L%20%3D%20Length%3B%20W%20%3D%20Width)
![Area = 27m^2](https://tex.z-dn.net/?f=Area%20%3D%2027m%5E2)
![L = 2W- 3m](https://tex.z-dn.net/?f=L%20%3D%202W-%203m)
Required
Find the dimensions of the rectangle
Area (A) is calculated as:
![A = L * W](https://tex.z-dn.net/?f=A%20%20%3D%20L%20%2A%20W)
This gives:
![27 = (2W - 3) * W](https://tex.z-dn.net/?f=27%20%3D%20%282W%20-%203%29%20%2A%20W)
Open bracket
![27 = 2W^2 - 3W](https://tex.z-dn.net/?f=27%20%3D%202W%5E2%20-%203W)
Express as a quadratic function
![2W^2 - 3W - 27 = 0](https://tex.z-dn.net/?f=2W%5E2%20-%203W%20-%2027%20%3D%200)
Expand
![2W^2 + 6W - 9W - 27 = 0](https://tex.z-dn.net/?f=2W%5E2%20%2B%206W%20-%209W%20-%2027%20%3D%200)
Factorize:
![2W(W + 3) - 9(W + 3) = 0](https://tex.z-dn.net/?f=2W%28W%20%2B%203%29%20-%209%28W%20%2B%203%29%20%3D%200)
![(2W - 9)(W + 3) = 0](https://tex.z-dn.net/?f=%282W%20-%209%29%28W%20%2B%203%29%20%3D%200)
This gives:
![2W - 9 = 0\ or\ W + 3 = 0](https://tex.z-dn.net/?f=2W%20-%209%20%3D%200%5C%20or%5C%20W%20%2B%203%20%3D%200)
![2W = 9 \ or\ W = -3](https://tex.z-dn.net/?f=2W%20%3D%209%20%5C%20or%5C%20W%20%3D%20-3)
Width can not be negative.
So:
![2W = 9](https://tex.z-dn.net/?f=2W%20%3D%209)
![W = 4.5](https://tex.z-dn.net/?f=W%20%3D%204.5)
Recall that:
![L = 2W- 3m](https://tex.z-dn.net/?f=L%20%3D%202W-%203m)
![L = 2 * 4.5 - 3](https://tex.z-dn.net/?f=L%20%3D%202%20%2A%204.5%20-%203)
![L = 6](https://tex.z-dn.net/?f=L%20%3D%206)
Answer:
x = 9
Step-by-step explanation:
Simplifying
17x + -12 = 114 + 3x
Reorder the terms:
-12 + 17x = 114 + 3x
Solving
-12 + 17x = 114 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
-12 + 17x + -3x = 114 + 3x + -3x
Combine like terms: 17x + -3x = 14x
-12 + 14x = 114 + 3x + -3x
Combine like terms: 3x + -3x = 0
-12 + 14x = 114 + 0
-12 + 14x = 114
Add '12' to each side of the equation.
-12 + 12 + 14x = 114 + 12
Combine like terms: -12 + 12 = 0
0 + 14x = 114 + 12
14x = 114 + 12
Combine like terms: 114 + 12 = 126
14x = 126
Divide each side by '14'.
x = 9
Simplifying
x = 9
Answer:
a) one solution
b) no solution
Step-by-step explanation:
Systems of equations can be described as having one solution, no solution or infinite solutions:
One solution: 'x' and 'y' are equal to only one value
No solution: 'x' and 'y' can not be solved with the given equations
Infinite solutions: values for 'x' and 'y' include all real numbers
In order to evaluate the systems, putting them in the same format is your first step:
a) - y = -5x - 6 or y - 5x = 6
y - 5x = -6
Since both equations have the same expression 'y - 5x', but there are equal to opposite values, this system would have no solution, as this would not be possible to calculate.
b) y + 3x = -1
y = 3x -1 or y - 3x = -1
Solving for 'y' by adding the equations and eliminating 'x', gives us:
2y = -2 or y = -1
Using y = -1 to plug back into an equation and solve for 'x': -1 + 3x = -1 or x = 0. Since 'x' and 'y' can be solved for a value, the system has just one solution.
Answer:
68
Step-by-step explanation: